Synthesis and antimycobacterial evaluation of new 5-(1-benzyl-1H-1,2,3-triazol-4-yl)-4-methyl-2-arylthiazole derivatives - Shinde, Vikas; Mahulikar, Pramod; Mhaske, Pravin C.; Chakraborty, Shakti; Choudhari, Amit; Phalle, Siddharth; Choudhari, Prafulla; Sarkar, Dhiman (Medicinal Chemistry Research, 2019)
A new series of 5-(1-benzyl-1H-1,2,3-triazol-4-yl)-4-methyl-2-arylthiazole derivatives, 6a-w have been synthesized by click reaction of substituted benzylazide, 5a-d with 5-ethynyl-4-methyl-2-substituted phenylthiazole, 4a-f. The starting compounds 4-ethynyl-2-substituted phenylthiazole (4a-f) were synthesized from the corresponding thiazole aldehyde by using the Ohira-Bestmann reagent. The structure of the synthesized compounds was determined by spectral analysis. All the synthesized compounds were screened for their preliminary antitubercular activity against Mycobacterium tuberculosis H37Ra (MTB, ATCC 25177). Most of the synthesized compounds reported good activity against M. tuberculosis H37Ra strain with IC50 range of 0.58-8.23 mu g/mL. Compounds 6g and 6k reported good antitubercular activity with MIC90 values of 4.71 and 2.22 mu g/mL, respectively. Potential antimycobacterial activity suggested that these compounds could serve as good lead compounds for further optimization and development of a newer antitubercular candidate. [GRAPHICS] .
Keywords: 1; 2; 3-Triazole; Antitubercular activity; Molecular docking; Ohira-Bestmann reagent; Thiazole

Exploring the pharmacological potentials of biosurfactant derived from planococcus maritimus SAMP MCC 3013 - Waghmode, Samadhan; Swami, Sagar; Sarkar, Dhiman; Suryavanshi, Mangesh; Roachlani, Sneha; Choudhari, Prafulla; Satpute, Surekha (Current Microbiology, 2020)
Therapeutic potential of biosurfactant (BS) has been improved in recent years. Our present study deals with production of BS from Planococcus maritimus SAMP MCC 3013 in a mineral salt medium (MSM) supplemented with glucose (1.5% w/v). Further, BS has been purified and partially characterized as glycolipid type through our previous publication. Current research article aimed to evaluate biological potential of BS against Mycobacterium tuberculosis, Plasmodium falciparum and cancerous cell lines. Planococcus derived glycolipid BS was found to be a promising inhibitor of M. tuberculosis (MTB) H37Ra at IC50 64.11 +/- 1.64 mu g/mL and MIC at 160.8 +/- 1.64 mu g/mL. BS also showed growth inhibition of P. falciparum at EC50 34.56 +/- 0.26 mu M. Additionally, BS also displayed the cytotoxicity against HeLa (IC50 41.41 +/- 4.21 mu g/mL), MCF-7 (IC50 42.79 +/- 6.07 mu g/mL) and HCT (IC50 31.233 +/- 5.08 mu g/mL) cell lines. Molecular docking analysis was carried for the most popular glycolipid type BS namely Rhamnolipid (RHL) aiming to interpret the possible binding interaction for anti-tubercular and anti-cancer activity. This analysis revealed the involvement of RHL binding with enoyl reductase (InhA) of M. tuberculosis. Docking studies of RHL with tubulin directed several hydrophobic and Vander Waal interactions to exhibit anti-cancer potential. The present study will be helpful for further development of marine bioactive molecules for therapeutic applications. Their anti-tubercular, anti-plasmodial and cytotoxic activities make BS molecules as a noteworthy candidate to combat several diseases. To the best of our knowledge, this is the first report on projecting the pharmacological potential of Planococcus derived BS. Graphic